Removal of Ferrous Ion in Synthetic Waters by Catalytic Air Oxidation - Engin, Bahadir; Guru, Metin; Alicilar, Ahmet (Asian Journal of Chemistry, 2010)
Catalytic air oxidation of ferrous ion in synthetic waters (Fe(NH4)2 (SO4)2·6H2O solution) was studied at neutral medium in batch reactors. Sepiolite, ZnO, NiO, MgO, Co3O4, MoO3., MnO2 and Al(OH)3 were separately used as catalyst. Iron(II) ion in water samples was analyzed by the bipyridine spectrophotometric method. Firstly, non-catalytic oxidation of Fe(II) in aqueous solution was investigated. However, low values of conversion percentage were obtained even if air was bubbled through the solution. An oxidation yield of 97 % was minimally obtained by resting only the solution at open air when an effective catalyst such as NiO was used. The activation energies were determined as 14.8 and 43.2 kJ/mol and the corresponding rate equations were obtained as -rA = 9.72 e-1779/T CA and -rA = 1672 e-5197/T CA for catalytic (NiO) and non-catalytic oxidation, respectively. The reaction order was found to be one with respect to Fe(II) concentration. Experiments were also conducted in a continuous system as a fixed bed reactor; however the obtained yields were very low.